Effect of Active Learning in Form of Scientific Approach with Assistance of Student Worksheets Based Problem Based Learning (PBL) Towards Students Biology Psychomotor Competence in Bacterial Material - Lufri, Lufri; Laili, Fitria; Anhar, Azwir (FKIP-Universitas Riau, 2020)
In the 2013 curriculum, students are demanded to be active in learning process. To actualize it, teacher should has adequate ability and skills by implementing appropriate learning model in teaching. Purpose of the research was to know effect of Active Learning in form of scientific approach with assistance of student worksheets based Problem Based Learning to wards students' Biology competence in Bacterial material. The research method used a quasi experimental research by using randomized control posted only design. The population was students in grade X MIPA of SMAN 1 Pasaman registered in academic year 2018/2019. Samples were taken by using Purposive Sampling technique. Instrument used was psychomotor competence observation sheet. Data analysis was conducted by using Mann Whitney U test. The finding showed that there is a significant difference between students' biology competence in experimental class and control class, in which students' biology competence in experimental class is higher than in control class. Average score of students' biology competence in experimental class is 3.34 (B+) and in control class is 3.17 (B). So, it can be concluded that Active Learning in form of scientific approach with assistance of student worksheets based Problem Based Learning can improve students Biology competence.